The impact of conversion on the risk of major complication following laparoscopic colonic surgery: an international, multicentre prospective audit. (25th September 2018) - ,
Abstract: Background: Laparoscopy has now been implemented as a standard of care for elective colonic resection around the world. During the adoption period, studies showed that conversion may be detrimental to patients, with poorer outcomes than both laparoscopic completed or planned open surgery. The primary aim of this study was to determine whether laparoscopic conversion was associated with a higher major complication rate than planned open surgery in contemporary, international practice. Methods: Combined analysis of the European Society of Coloproctology 2017 and 2015 audits. Patients were included if they underwent elective resection of a colonic segment from the caecum to the rectosigmoid junction with primary anastomosis. The primary outcome measure was the 30‐day major complication rate, defined as Clavien‐Dindo grade III‐V. Results: Of 3980 patients, 64% (2561/3980) underwent laparoscopic surgery and a laparoscopic conversion rate of 14% (359/2561). The major complication rate was highest after open surgery (laparoscopic 7.4%, converted 9.7%, open 11.6%, P < 0.001). After case mix adjustment in a multilevel model, only planned open (and not laparoscopic converted) surgery was associated with increased major complications in comparison to laparoscopic surgery (OR 1.64, 1.27–2.11, P < 0.001). Conclusions: Appropriate laparoscopic conversion should not be considered a treatment failure in modern practice. Conversion does not appear to place patients at increased risk of complications vs planned open surgery, supporting broadening of selection criteria for attempted laparoscopy in elective colonic resection.